PENERAPAN TEKNOLOGI FERMENTASI PADA BIOPROSES FERMENTASI MINYAK KELAPA (FERMIKEL) [Bioprocessing of Fermented Coconut Oil by Application of Fermentation Technology] - Sulistyo, Joko; Soeka, Yati Sudaryati; Triana, Evi; Napitupulu, Rostiati NR; Joko Sulistyo (Research Center for Biology-Indonesian Institute of Sciences, 1999)
Methods of extracting oil from coconut endosperm by fermentatbn were studied. The factors which must be controlled to break the emulsion and liberate oil were investigated. It was found that grinding conditions exerted a profound effect upon the stability of the coconut milk emulsion. The optimum condition for rapid fermentathn of coconut milk was related to the condition during incubation period. The fermentation progressed best under mild conditions (28Â°C-40Â°Cj. The fermentation was successful in breaking the emulsion at a relatively broad of range and titrable acidity. Coconut cream and small volume of coconut water and